Ultra-processed Food Consumption by Pregnant Women: The Effect of an Educational Intervention with Health Professionals - Gomes, Caroline de Barros [UNESP]; Malta, Maíra Barreto; Louzada, Maria Laura da Costa; Benício, Maria Helena D’Aquino; Barros, Aluísio J. D.; Carvalhaes, Maria Antonieta de Barros Leite [UNESP] (Springer Nature, 2019)
Objectives Nutrition during pregnancy is related with many maternal and child outcomes. To investigate the consumption of ultra-processed foods is one of the newest methods to evaluate food consumption, but these studies in pregnant women are rare. Methods We conducted a non-randomized controlled educational intervention on healthy eating and physical activity during pregnancy in primary health care units of Botucatu, São Paulo, Brazil. The sample comprised two groups of pregnant women with low obstetric risk, an intervention group (n = 181) and a control group (n = 172). The health professionals that assisted the pregnant women from the intervention group were trained to promote five healthy food practices during the prenatal care appointments: consumption of three fruits; two portions of vegetables; two portions of beans, at least 5 days per week; and restriction of soft drinks and industrially processed cookies. All pregnant women answered two 24-h dietary recalls per trimester, one face-to-face, another by telephone. The foods consumed by pregnant women were classified according Nova. The impact of the intervention on the ultra-processed food consumption was evaluated by multilevel linear regression analysis. Results A quarter of the energy consumed by the pregnant women provided from ultra-processed foods. The intervention reduced these percentage of energy between the first and second trimester of pregnancy by 4.6 points (p = 0.015). This effect was not observed in the third trimester of pregnancy. Conclusions for Practice Training health care professionals to promote healthy food practices is a viable and sustainable alternative to reduce ultra-processed foods during pregnancy.
Keywords: Dietary modifications; Educational intervention; Pregnancy; Pregnant women; Ultra-processed foods